BEYOND STANDARD RISK FACTORS: THE GENETIC AND ANAMNESTIC PROFILE OF PATIENTS WITH SEVERE PREECLAMPSIA IN THE UZBEK POPULATION - Radjabova Zulola Abduhakimovna (Scholar Express Journal, 2025)
To analyze the clinical-demographic characteristics, latent risk factors, and genetic predictors of severe preeclampsia (PE) as a form of secondary thrombotic microangiopathy (TMA)
Keywords: Preeclampsia; thrombotic microangiopathy; pregnancy